La expresión corporal en el desarrollo del equilibrio dinámico en los niños de 5 a 6 años del centro Educativo Vigotsky, de la ciudad de Riobamba Provincia de Chimborazo año lectivo 2015 – 2016 - Andrade Calvopiña, Lesly Carolina (2016)
The importance of Corporal Expression in the Development of Dynamic Balance in children aged 5 to 6 is presented, taking into account that training in these two aspects are the basis to connect children with the world that surround them, especially the influence of the child in early education classrooms, setting characteristics, elements and games are encouraged. This helps to a better understanding of space by children, taking as a starting point internalizing feelings. We sought to make proposals for action in the classroom based on corporal expression realated to the dynamic equilibrium to influence aspects of body, children in the evolutionary process are anxious to learn new ways to navigate because it is normal curiosity in them and better at these ages motivate them ti speak freely with his body; this research contains objectives,certain variables and instruments for data collection, the same as was tabulated, processed, analyzed and supported by the theoretical framework considering conclusions and recommendations. Within the methodology used to conduct this worked scientific, deductive,inductive method, research, descriptive and explanatory type, a research field level, documentary and non-experimental was used was considered, information was collected from 35children observed and applied an interview to the teacher, the determination of independent and dependent variables; where the problema is diagnosed through a situational analysis; where certain weaknesses are verified in the development activities involving corporal expression in the development of dynamic equilibrium, it has been estimated that most children performend coordinated movements, encouraging them to engage in activities that form habits of movement which will help them to their interaction in the surrounding environment.